Consortium of Microalgae for Tannery Effluent Treatment - Pena,Aline de Cassia Campos (2019)
Abstract Wastewater generated in tanneries have essential elements for microalgae growth, but it has also some toxic compounds that may hinder or restrain the growth of microalgae in this environment. This work tested microalgae consortium growth originating from a deactivated effluent treatment decanter of a complete tannery (beamhouse to finished leather) for the treatment of wastewater of a tannery processing wet-blue leather to finished leather. It was initially evaluated the growth of the microalgae consortium in the three effluents diluted in 50% distilled water: raw effluent (50RE50W), effluent after primary coagulation/flocculation (50PE50W), and effluent after primary and secondary biological treatment (50BE50W). After 16 days of cultivation, the 50PE50W presented the highest biomass concentration (1.77 g L−1). The highest removal values for effluents 50RE50W, 50PE50W and 50BE50W were 51.02%, 99.90%, 82.88%, and 91.75% for chemical oxygen demand (COD), N-NH3, TKN, and P-PO4-, respectively. It was verified low levels of nutrient removal in the raw effluent (100RE), since the consortium was not able to grow in this medium. Finally, at concentrations of 25RE75BE (25% raw effluent diluted with 75% effluent after the biological treatment) and 50RE50B (50% raw effluent diluted with 50% effluent after the biological treatment), effective removal values were reached. Biomass growth concentration up to 1.3 g L-1 and removal values for N-NH3, TKN, P-PO4, COD, total organic carbon (TOC) and biological oxygen demand (BOD5), of 99.90%, 79.36%, 87.82%, 14.26%, 35.82%, and 42.86%, respectively, were reached in 50RE50B.